Performance of PTFE-Based Adaptive Building Facades for Climate Resilience: A Simulation-Driven Analysis - Antima Kuda; Madhura Yadav; Syed Moazzam Ali (Malikussaleh University, Aceh, Indonesia, 2025)
As an aesthetic architectural thermal barrier, the building envelope is considered vital and contributes substantially in improving the overall building performance. Responsive Facades bring in a revolutionary transformation to the static building skins by changing it into an adaptive façade that responds to the external climatic conditions like solar heat gain, light and temperature variations. The key objective of the paper is to evaluate the potential of PTFE (Polytetrafluoroethylene) in enhancing the building energy efficiency and thermal comfort index of the users in comparison to a static, Energy Conservation Building Code (ECBC) compliant base case test model, under identical environmental conditions. Evaluation is based on the simulation analysis conducted on the highrise office building in Jaipur, India a region characterized by a composite climate with hot summers and cold winters. The complete assessment is derived by using DesignBuilder V7.0 with Energyplus engine. This research focuses on the performance of PTFE as a climate responsive material when used in adaptive building envelopes. Performance metrics include annual heating, ventilation, and air conditioning HVAC energy consumption (kWh/m²), thermal discomfort hours, Predicted Mean Vote (PMV), and Predicted Percentage of Dissatisfied (PPD). Results demonstrate that the ECBC-compliant static facade recorded an annual HVAC energy use of 96 kWh/m², 1,588 discomfort hours, a PPD of 25.3%, and PMV of +0.82. In comparison, the PTFE kinetic facade achieved an energy use reduction to 95 kWh/m² (1.3% lower), reduced discomfort hours to 1,532 and improved thermal comfort with a PPD of 24.1% and PMV of +0.76. These findings have highlighted the uniqueness of Responsive facades while analysing their capability in enhancing the thermal comfort index and lowering energy consumption, supporting sustainable and climate-responsive building design.